Participatory approach to crop improvement at the community level in Vietnam - Nguyen, Ngoc De (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Crop improvement has been one of the strong, continuous programs in the Mekong Delta for major crops, especially rice. However, most breeding programs have been set and designed by breeders, neglecting the role of users: farmers and farming communities. Farmers have been the passive users, receiving finished breeding lines varieties for their production. The dissemination process of “technology transfer" has been very slow and costly for both breeders and farmers.